The Role of Monocyte Chemoattractant Protein-1 (MCP-1) in Diabetic Kidney Disease - Deddy Canceria Suka Rahmatsyah; Harnavi Harun; Deka Viotra (HM Publisher, 2023)
Monocyte chemoattractant protein-1 plays an important role in kidney disease. In several studies, the role of MCP-1 as a urine biomarker has been extensively studied. In many kidney diseases, there are elevated levels of MCP-1 in the kidney tissue and this is an important cause of monocyte infiltration in the pathogenesis of kidney damage. Elevated urinary MCP-1 levels have been able to predict outcome in proliferative kidney diseases such as lupus nephritis. However, in several studies it was also found that there was an increase in MCP-1 in diabetic kidney disease. Macrophages have even appeared early in diabetic kidney disease and are associated with the progression of kidney disease. Urinary MCP-1 levels are related to the degree of leukocyte infiltration in the tubulointerstitial. This supports inflammatory factors as part of the pathogenesis of diabetic kidney disease.